Project-based method in teaching foreign language for specific purposes - Bolsunovskaya; Ludmila M.; Korotchenko; Tatiana V.; Matveenko; Irina Alexeevna; Strelnikova; Anna B.; Ulyanova; Oksana S.; Phillips; Chris (Procedia - Social and Behavioral Sciences, 2015)
This paper considers the innovative methods of teaching Foreign Language for Specific Purposes. The methods are intensively implemented in teaching 3–4-year students at the Institute of Natural Resources Tomsk Polytechnic University (TPU) Russia. In particular the paper presents the international project “Approaching the Arctic” developed in cooperation with NTNU (Norwegian University of Science and Technology) Norway. This paper analyzes the efficiency of the implementation of the project-based method in teaching English for Specific Purposes.